Enhancing Investment Acumen through Web-Based Capital Market Seminars: A Case Study in Probolinggo - Hermanto Hermanto; Nurul Izzah (Indonesian Journal of Cultural and Community Development, 2023)
This study aimed to enhance the understanding of stock investment principles, specifically technical and fundamental analysis, among beginners in the capital market. Using a web seminar format, the research incorporated socialization methods, engaging investment managers as speakers and a diverse audience of students and lecturers from Probolinggo. An interactive question-answer session was employed to gauge the participants' comprehension. The learning outcomes were evaluated via pre- and post-tests, revealing significant improvements in participants' understanding of technical and fundamental analysis for stock investment. The study underscores the effectiveness of web seminars in fostering informed decision-making in the capital market, thereby minimizing the selection of risky stocks. Consequently, this approach could serve as a valuable tool in global financial education and investment literacy efforts.Highlights: The web seminar effectively fostered investment literacy, highlighting the importance of digital platforms in financial education. Participants showed significant improvement in understanding technical and fundamental analysis, underscoring the seminar's impact on investment decision-making skills. The study's results imply a minimized selection of risky stocks, hinting at the potential of such educational efforts in enhancing global financial stability. Keywords: Web Seminar, Stock Investment, Capital Market, Fundamental Analysis, Technical Analysis.